2004
DOI: 10.1158/0008-5472.can-03-3504
|View full text |Cite
|
Sign up to set email alerts
|

HER-2, gp100, and MAGE-1 Are Expressed in Human Glioblastoma and Recognized by Cytotoxic T Cells

Abstract: It has recently been demonstrated that malignant glioma cells express certain known tumor-associated antigens, such as HER-2, gp100, and MAGE-1. To further determine the possible utilization of these antigens for glioma immunotherapy and as surrogate markers for specific tumor antigen cytotoxicity, we characterized the presence of mRNA and protein expression in 43 primary glioblastoma multiforme (GBM) cell lines and 7 established human GBM cell lines. HER-2, gp100, and MAGE-1 mRNA expression was detected in 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(115 citation statements)
references
References 35 publications
3
109
3
Order By: Relevance
“…So far, T-cell epitopes derived from SART-1 and -3 (Imaizumi et al, 1999;Murayama et al, 2000), IL-13 receptor a2 chain (Okano et al, 2002), ADPribosylation factor 4-like (ARF4L) , UDP-Gal: betaGlcNAc beta1, 3-galactosyltransferase, polypeptide 3 (GALT3) , AIM-2 (Liu et al, 2004a), EphA2 (Hatano et al, 2005) and the type III variant of the epidermal growth factor receptor (EGFRvIII) (Wu et al, 2006) have been described. In addition, it has been shown that HER-2, gp100, MAGE-1 and TRP-2 were expressed in glioma and were recognised by CTLs (Liu et al, 2003(Liu et al, , 2004b. However, the suitability of some candidates for specific immunotherapy of glioma is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, T-cell epitopes derived from SART-1 and -3 (Imaizumi et al, 1999;Murayama et al, 2000), IL-13 receptor a2 chain (Okano et al, 2002), ADPribosylation factor 4-like (ARF4L) , UDP-Gal: betaGlcNAc beta1, 3-galactosyltransferase, polypeptide 3 (GALT3) , AIM-2 (Liu et al, 2004a), EphA2 (Hatano et al, 2005) and the type III variant of the epidermal growth factor receptor (EGFRvIII) (Wu et al, 2006) have been described. In addition, it has been shown that HER-2, gp100, MAGE-1 and TRP-2 were expressed in glioma and were recognised by CTLs (Liu et al, 2003(Liu et al, , 2004b. However, the suitability of some candidates for specific immunotherapy of glioma is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ARF4L and GALT3 were markedly expressed in various normal tissues Tsuda et al, 2002) bearing the potential risk of autoimmune reactions. In addition, gp100, MAGE-1, TRP-2 and EGFRvIII were detectable only in a part of gliomas restricting the number of potentially treatable patients (Chi et al, 1997;Liu et al, 2003Liu et al, , 2004bBiernat et al, 2004). Owing to these limitations of several glioma-associated antigens and the heterogeneity of different types of malignant glioma (Chi et al, 1997;Nagane et al, 1997;Liang et al, 2005), the identification of additional target structures for CTLs is required.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in vivo treatment of HMW-MAAnegative melanoma lesions with DAC or other epigenetic modulators could induce HMW-MAA expression, thus increasing the efficacy of antigen-specific antibodies and T cells. In support of the latter possibility, potentiation of tumor antigen recognition following DAC treatment has been shown in other systems, and may serve as a generally applicable mechanism to increase tumor antigen recognition by the immune system (Serrano et al, 2001;Karpf and Jones, 2002;Liu et al, 2004). However, the possible role of HMW-MAA in tumor metastasis serves as a cautionary note for the use of DNA methyltransferase inhibitors to activate anti-tumor immunity targeting HMW-MAA.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies have shown that melanomaassociated antigens, such as TRP-2, MAGE-1 and gp100 are not only expressed on glioblastoma tumor cells but also may be naturally processed and recognized by cytotoxic T-cells in an MHC class I restricted manner (Liu et al, 2003(Liu et al, , 2004b. TRP-2 may be a unique target molecule for cancer vaccines because TRP-2 expression is not only a highly immunogenic tumor antigen but is also associated with chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%